2019
DOI: 10.1055/a-0895-5166
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance in Adults with Type 1 Diabetes is Associated with Lower Vitamin D Serum Concentration

Abstract: Aim Type 1 diabetes mellitus (T1DM) is a disease characterized by an absolute deficiency of endogenous insulin secretion. Insulin resistance (IR) may develop among patients with T1DM. Vitamin D deficiency was reported to be a risk factor in the development of IR. The aim of the study was to assess the relationship between serum concentrations of 25-hydroxyvitamin D (25(OH)D) and IR among patients with T1DM. Methods The test group consisted of 110 adult patients [males=65 (59%)] with T1DM. Participants were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…VD deficiency and VD receptor polymorphisms were previously reported to be potential risk factors of developing T1DM [17,18]. Moreover, our observation revealed that VD serum concentration is negatively associated with insulin resistance in adults with T1DM [19]. In the same study, Kamiński et al reported that 47% of adults with T1DM had VD deficiency (25(OH)D) < 20 ng/mL) and 15% had VD severe deficiency (25(OH)D) < 10 ng/mL)in the period of limited insolation in Poland.…”
Section: Introductionsupporting
confidence: 60%
“…VD deficiency and VD receptor polymorphisms were previously reported to be potential risk factors of developing T1DM [17,18]. Moreover, our observation revealed that VD serum concentration is negatively associated with insulin resistance in adults with T1DM [19]. In the same study, Kamiński et al reported that 47% of adults with T1DM had VD deficiency (25(OH)D) < 20 ng/mL) and 15% had VD severe deficiency (25(OH)D) < 10 ng/mL)in the period of limited insolation in Poland.…”
Section: Introductionsupporting
confidence: 60%
“…Functionally, sufficient serum 25(OH)D concentration can preserve the activity of residual pancreatic β-cells and insulin secretion [44]. Meanwhile, a past study reported that the serum 25 (OH)D concentration was negatively associated with insulin resistance in patients with T1DM [45]. Children with T1DM have also been reported to have lower 25(OH)D concentration than healthy children [5].…”
Section: Discussionmentioning
confidence: 99%
“…There is much less data available regarding adult patients with T1D. It has been observed that the serum concentration of VD is negatively associated with IR in adult diabetic patients recruited in Poland [37]. In Algerian population, the link between VD deficiency and an increased risk of T1D was also found [38].…”
Section: Vitamin D Deficiency and Type 1 Diabetes Mellitusmentioning
confidence: 99%